Correction of psycho-emotional stress among primary schoolchildren with special educational needs with the use of biofeedback - R. A. Kistenyova; Yu. V. Kistenyov; Ya. S. Pekker; K. S. Brazovskiy; N. G. Brazovskaya; V. A. Fokin (Бюллетень сибирской медицины, 2010)
The peculiarities of correction of psycho-emotional stress among primary schoolchildren with special educational needs with the use of biofeedback on the basis of statistic analysis of the heart rate are presented. The methodology developed by the authors is realized in the hardware-software complex «Boston». Results of the conducted research have shown that the use of BOS-training leads to definite reduction of psycho-emotional stress as well as to improvement of activity indicators among children with special educational needs.